Study of the Effectiveness of Interactive Learning Media in Islamic Religious Education Subjects and Its Function in Increasing Active Student Participation - Husna Husna; Mahmoud Abdullah; Helene Knudstad; Md. Sultan Mahmud; Khalid Abdullah Al Muzaini (Al Husna: Jurnal Ilmiah Pendidikan Agama Islam, 2024)
This research aims to evaluate the effectiveness of interactive learning media in Islamic Religious Education (PAI) subjects and its function in increasing students' active participation. It is hoped that interactive learning media can create a more interesting and dynamic learning environment, so that students are more motivated to be actively involved in the learning process. The research method used is quantitative with an experimental approach, which involves collecting data through observation, questionnaires and interviews. The research results show that the use of interactive learning media, such as digital educational applications, learning videos, and educational games, significantly increases students' active participation in PAI classes. This interactive media also helps students understand subject matter better and develop critical thinking skills. However, this research also identified challenges in implementing interactive learning media, including limited access to technology and teachers' lack of skills in utilizing this media. Therefore, it is recommended that there be increased access to technology in schools and ongoing training for teachers to optimize the use of interactive learning media. Thus, interactive learning media can function more effectively in increasing students' active participation and enriching their learning experience